(untitled) (IUBAT Review, 2023)
Plant protection equipment is essential in the agricultural field for increasing crop productivity and minimizing the losses caused. Specialized machinery for mechanically applying chemicals is crucial for maximizing crop yields in farming. Farmers use a wide range of pesticides to counteract the effects of insects, diseases, and fungi on their crops. The backpack sprayers do the spraying with staffing, which requires more human effort, covers a small area, is time-consuming, and has a low storage capacity. The market introduced many products to address these limitations, but they cannot work simultaneously. Solar, electrical, and chemical energy is now being used to spray pesticides, but these methods are expensive and require a trained operator. To address the issues above, a product designed with adaptable spraying equipment is proposed to benefit medium-and small-scale farmers. This study aims to look at the problem of manual backpack sprayers and reduce backpack and foot spraying, eliminate human efforts, and decrease labor costs by advancing the spraying method and a constant flow of droplets. Finally, we have investigated the effects of urging gardeners and farmers to spray their plants with liquids such as pesticides, herbicides, and water. The proposed design can help gardeners in terms of comfort during spraying, reducing energy used to pump tanks, and effectively utilizing spraying time. IUBAT Review—A Multidisciplinary Academic Journal, 6 (1): 88-99